Efektivitas Sanksi Administratif Kppu Dalam Penegakan Pasal 23 Undang-Undang No. 5 Tahun 1999 (Analisa Perkara Nomor 08/Kppu-L/2024 entang Dugaan Persekongkolan untuk Mendapatkan Rahasia Perusahaan) - Widagdo, Deztu Ramadyto; Widagdo, Gatot Subroto (Neolectura, 2026)
This study aims to analyze the legal reasoning underlying the imposition of administrative sanctions by the Business Competition Supervisory Commission (KPPU) in Case Number 08/KPPU-L/2024 concerning the violation of Article 23 of Law Number 5 of 1999 on conspiracy to obtain trade secrets, as well as to evaluate the effectiveness of such sanctions in creating a deterrent effect and preventing similar violations in the future. The research focuses on the repressive, preventive, and educative functions of administrative sanctions within the framework of trade secret protection and competition law enforcement. This research employs a normative juridical method with descriptive and evaluative characteristics. The approach involves an analysis of relevant legal norms, principles, and doctrines, as well as a comprehensive examination of KPPU Decision Number 08/KPPU-L/2024. Data were analyzed qualitatively by assessing the conformity of the application of Article 23 of Law No. 5 of 1999 with the legal framework governing trade secrets under Law No. 30 of 2000, using the theory of legal effectiveness as the analytical framework. The findings indicate that the Commission Panel, in imposing administrative sanctions, considered the elements of conspiracy, the degree of fault, the impact on business competition, and the principle of proportionality. Normatively, the sanctions imposed comply with applicable legal provisions. However, in terms of effectiveness, the deterrent impact of administrative sanctions requires further strengthening, particularly in implementation and in enhancing legal awareness among business actors. The study concludes that although the administrative sanctions fulfill their repressive function, their preventive and educative effectiveness largely depends on consistent law enforcement and regulatory reinforcement to ensure stronger protection of trade secrets within Indonesia’s competition law regime.